An Overview of General Regulations to Minimize Environmental Affects from Petroleum Drilling and Production Activities - Al-Haleem, Ayad; Al-Mahdawi, Faleh (Iraqi Journal of Science, 2023)
Improved environmental protection requires better education and training of regulations which manage different available activities in petroleum operations.Data from industry is very important to ensure that the existing or suggested regulations are based on accurate scientific information and that they contribute to best environmental protection without adding useless restrictions to this industry.This research deals with an overview of major environmental regulations and issues facing the petroleum industry.Many issues which regulate drilling and production activities that may pollute surface water, clean up of existing hazardous waste sites, storage and management of various chemicals and other important aspects are listed and discussed to know how to protect our petroleum environment by minimize or eliminate the adverse impacts through the understanding and implementation of proper regulations management.